Kultur Damai Berbasis Tradisi Pela Dalam Perspektif Psikologi Sosial - Ralahallo, Roubrenda N. (Faculty of Psychology, Universitas Gadjah Mada, 2009)
Conflict and violence was the destructive reality that showed reduction and alienated of existence humanity. The essence of human being has destruction because dominance of egoism of peopleâ€™s without care value of victim community. Because of that condition, the basic need to create a culture of peace as constructive reality that connected relationship between all of people is urgently. On the level individual and group, the acceptance of â€œthe otherâ€selfâ€ as him/herself has destroy the wall of differences which always be source of conflict and violence. The fusion identity â€œweâ€ (ingroup) and â€œthemâ€ (outgroup) has establish common ingroup identity as â€œusâ€ in recategorization process that contribution to reduction negative aspect seems like prejudice, discrimination and stereotype. This research involve four subject with age 20â€30 years old, genre as masculin and feminin, and they have a comprehensive science about pela tradition. Other informant like a King of negeri, Kapitan negeri and all of people also involve in this research. Qualitative method with ethnoâ€phenomenology approach is use in this research with observation and interview as method and procedure to collect data. The result of this research showed that culture of peace can be found in local wisdom as pela tradition. The basic idea in this tradition is a common identity â€œsaudara/orang basudaraâ€ which has calling as â€œelaâ€. Pscychological dynamics occur in this perspective because the word of â€œelaâ€ to contain a constructive and positive meaning that arranged relation between the groups Rohomoniâ€Tuhaha. Implementation of values the culture of peace has been seen in the behavioral â€œsaudara pelaâ€ that mutual constructive, trust, respect. This fact could be found in Molluccas conflict at 1999â€2004, pela tradition can be the media reconciliation between two groups Moslem and Christian.